Gender roles in the fang family concept: a differential socialization system - Bituga-Nchama, Pedro (2021)
This article focuses on making visible the gender roles, products of the differential socialization of the concept of the Fang family. This fundamental objective shows that since the family is an institution where the first socialization of people takes place, the Fang family model is not far from this standard, because the way of socialization within this culture makes men be assigned different roles than women. This is notably seen in the sexual division of labor that is very present in the concept of the Fang family, thus perpetuating the differential socialization system that drives and aggravates social inequalities, motivated by sex-gender. In this sense, we find that domestic tasks and private space correspond exclusively to women, while men occupy public space. A society governed by this differential socialization system creates an imbalance where women end up being minimized. In order to better study this issue, a quantitative methodology has been used, based on the descriptive method, which has made it possible to reflect the incidence of this phenomenon in the selected population group. This research reaffirms that traditional gender roles are promoted in different ways within the concept of the Fang family, fostering an education of dependence, where the cognitive and personal skills of women are always undervalued by the Fang patriarchal system.